EDUKASI ISI PIRINGKU DENGAN METODE PENDEKATAN PEMBUATAN SALAD BUAH SEGAR DI SMP YARI PADANG - Nadia Purnama Dewi; Zuhrah Taufiqa; Ade Teti Vani; Irwan Triansyah; Dessy Abdullah; Aryaldi Zulkarnaini (Nusantara Hasana Journal, 2024)
Motivation/Background: Good nutritional knowledge is crucial for teenagers to support optimal growth and development. Comprehensive nutrition education is very important for teenagers to understand the importance of a balanced diet, according to the "Fill My Plate" concept. This service activity aims to increase junior high school student's understanding of balanced nutrition using an approach to making fresh fruit salad. Method: The service method is in the form of counseling and workshops. Counseling on “Fill My Plate” which includes the ideal proportions of various food groups. The workshop consists of practicing making fruit salad (selecting fruit variations) and finishing the fruit salad that has been made, as the core activity. Results: During the workshop, 100% of students were able to make fruit salad variations that followed the content of the counseling and fruit-eating challenge. 2 people out of 37 students who attended did not finish their fruit. Conclusion: This service concludes that this program has succeeded in instilling awareness about the importance of healthy eating patterns from an early age, as well as providing practical skills that can be applied in everyday life